Process of identifying bodies in the framework of the Justice and Peace project at the Forensic Genetics Laboratory of the National Institute of Legal Medicine and Forensic Sciences, Southwest Regional Office, between October 17, 2008 and June 21, 2012 (2015)
Introduction: A critical part of the Justice and Peace project focuses on findingand identifying victims of forced disappearance in Colombia in order to re-bury them according to local traditions and, generally, to provide full reparation to their families, according to Article 44 (45.5) of Law 975/2005. Methodology: The Forensic Genetics Laboratory of the National Institute of Legal Medicine and Forensic Sciences, Southwest Regional Office in Cali, makes its contribution to the process of identification by verifying biological kinship relations between the remains exhumed and the biological samples taken from alleged relatives of the victims. Results: Such process of identification is evaluated in this article based on a review of this kind of cases analyzed in the period between October 17, 2008 and June 21, 2012, in order to establish the impact of its contribution and verify its effectiveness. Conclusions: Possible improvements are proposed for guiding cases and for the effectiveness and efficiency in carrying out activities at each stage of the process.